2016
DOI: 10.7863/ultra.15.01082
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Diaphragmatic Excursion and Thickness in Healthy Infants and Children

Abstract: This study provides reference values for diaphragmatic excursion and thickness in healthy infants and children. Percentile curves for right diaphragmatic excursion plotted against body weight were plotted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
63
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 32 publications
(60 reference statements)
10
63
2
11
Order By: Relevance
“…To our knowledge, our study is the first one evaluating all the evaluable parameters in every single patients and the only one evaluating otherwise healthy pediatric patients with respiratory conditions. In fact, in current literature we found three studies conducted on pediatric ill patients (either post operative or mechanically ventilated patients), and only one study on pediatric healthy patients . Using these last literature parameters and comparing them to our findings, we found that mean right DE was 10.38 ± 4 mm in our bronchiolitis patients compared to 6.4 ± 2.1 in healthy reference children.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…To our knowledge, our study is the first one evaluating all the evaluable parameters in every single patients and the only one evaluating otherwise healthy pediatric patients with respiratory conditions. In fact, in current literature we found three studies conducted on pediatric ill patients (either post operative or mechanically ventilated patients), and only one study on pediatric healthy patients . Using these last literature parameters and comparing them to our findings, we found that mean right DE was 10.38 ± 4 mm in our bronchiolitis patients compared to 6.4 ± 2.1 in healthy reference children.…”
Section: Discussionsupporting
confidence: 53%
“…In fact, in current literature we found three studies 61,64,65 conducted on pediatric ill patients (either post operative or mechanically ventilated patients), 67 and only one study on pediatric healthy patients. 68 Using these last literature parameters and comparing them to our findings, we found that mean right DE was 10.38 ± 4 mm in our bronchiolitis patients compared to 6. We acknowledge some limitations.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Num estudo prospetivo transversal, 14 foram estabelecidos valores de referência segundo a idade para a espessura diafragmática, em crianças saudáveis. No nosso estudo, a mediana da espessura inicial foi de 2,3 mm, encontrandose abaixo do valor médio de referência para qualquer faixa etária.…”
Section: Discussionunclassified